2015
DOI: 10.3390/jfb6020259
|View full text |Cite
|
Sign up to set email alerts
|

Using Magnetic Nanoparticles for Gene Transfer to Neural Stem Cells: Stem Cell Propagation Method Influences Outcomes

Abstract: Genetically engineered neural stem cell (NSC) transplants offer a key strategy to augment neural repair by releasing therapeutic biomolecules into injury sites. Genetic modification of NSCs is heavily reliant on viral vectors but cytotoxic effects have prompted development of non-viral alternatives, such as magnetic nanoparticle (MNPs). NSCs are propagated in laboratories as either 3-D suspension “neurospheres” or 2-D adherent “monolayers”. MNPs deployed with oscillating magnetic fields (“magnetofection techno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 39 publications
(55 reference statements)
0
28
0
Order By: Relevance
“…We recently reported technically simple, rapid and safe magnetofection protocols for genetic modification of major neural transplant types including NSCs, with oscillating magnetic fields always outperforming static fields [21][22][23][24][25]. MNPs have emerged strongly as a class of advanced functional materials for neuro-regeneration, serving as 'multifunctional tools' for cell therapy given additional applications for non-invasive cell imaging and magnetic cell targeting, so it is clear that this non-viral gene transfer method offers significant benefits for clinical translation [26].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 4 more Smart Citations
“…We recently reported technically simple, rapid and safe magnetofection protocols for genetic modification of major neural transplant types including NSCs, with oscillating magnetic fields always outperforming static fields [21][22][23][24][25]. MNPs have emerged strongly as a class of advanced functional materials for neuro-regeneration, serving as 'multifunctional tools' for cell therapy given additional applications for non-invasive cell imaging and magnetic cell targeting, so it is clear that this non-viral gene transfer method offers significant benefits for clinical translation [26].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…MNPs have emerged strongly as a class of advanced functional materials for neuro-regeneration, serving as 'multifunctional tools' for cell therapy given additional applications for non-invasive cell imaging and magnetic cell targeting, so it is clear that this non-viral gene transfer method offers significant benefits for clinical translation [26]. Despite the critical advantages offered by this technique, we and others have reported that DNA plasmid size bears an inverse relationship with transfection efficiency for non-viral methods such as liposome-and nanoparticle-mediated transfection [23,[27][28][29]. For example, using lipofection, a systematic analysis of luciferase expression levels (using reporter constructs of increasing size; 4.8 kb to 10.5 kb) showed reduced transfection with greater plasmid size [29].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations